The Suprameatal Dural Flap for Superior Petrosal Vein Protection during the Retrosigmoid Intradural Suprameatal Approach - Mortini, Pietro; Gagliardi, Filippo; Boari, Nicola; Spina, Alfio; Bailo, Michele; Franzin, Alberto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Object The drilling of the suprameatal bone during the retrosigmoid intradural suprameatal approach (RISA) puts the superior petrosal vein complex at risk of heating and mechanical injury, which may lead to cerebellar swelling and infarction. We present a new technique to protect the superior petrosal venous complex during suprameatal bone drilling.Material and methods A microanatomical laboratory investigation on cadaver was conducted. The surgical technique is described and intraoperative schematic pictures are provided.Results The surgical steps of this technique and the related intraoperative images are reported. One case illustration regarding the removal of a large petrous apex meningioma with Meckel cave extension is described to demonstrate the application of the technique in a clinical setting.Conclusions Reflecting a dural flap onto the posterior trigeminal nerve root and the superior petrosal vein complex can be a simple way to protect the nerve and the vein during the suprameatal bone drilling during the RISA.
Keywords: retrosigmoid intradural suprameatal approach; petrosal vein; trigeminal nerve; cerebellopontine angle; Meckel cave